Variability in Assessment of Preclinical Prosthodontics Work of Undergraduate Student - Mohamed Elmaroush*; Sarra Ben Hamida; Zieneb Elgarboae; Narjes Mohsen (Khalij-Libya Journal of Dental and Medical Research, 2022)
Background and objective. Clinical professions are often concerned not just on the knowledge acquisition, but achievement of skills and their application. Assessment tools employed in preclinical prosthodontic training vary widely, the two most common being used are the glance and grading method and the objective check list criteria, and any assessment procedure employed should be transparent in manner with both the staff and students informed of the purpose and the process adopted. This study was undertaken to examine whether introduction of an objective scoring criteria can improve the validity of scoring in assessment of preclinical prosthodontics (bite block) that done by students. Methods. The study evaluated 240 undergraduate students who were in second year of study at dental school Tripoli University, performing a bite block (trial denture base with wax rim) performed on ideal stone cast. The preclinical work (bite block) were evaluated and allotted marks by four blinded independent examiners using two methods of scoring, glance and grade method and objective checklist scoring method. Results. The data were parametric and met the normal distribution. Therefore, the scores were presented by mean and standard deviation. There was a significant difference (p value less than 0.005) between two scoring methods of preclinical prosthodontics work (glance and grade and objective checklist methods). Conclusion. This study concludes by recommending that preclinical prosthodontics work of students be assessed by objective checklist criteria scoring and it should be introduced after sufficient training and calibration sessions to induce examiner reliability. Citation: Elmaroush M, Ben Hamida S, Elgarboae Z, Mohsen N. Variability in Assessment of Preclinical Prosthodontics Work of Undergraduate Student. Khalij-Libya J Dent Med Res. 2022;6(2):129–133. https://doi.org/10.47705/kjdmr.2262007